The measurement and field experiment design of soil erosion / Mohd Fozi Ali - Ali, Mohd Fozi (2002)
Soil erosion is one of the critical problems in Southeast Asia, mainly due to high rainfall intensities, poor soil condition, improper land use management and practice, particularly in upland agriculture. Soil loss creates environmental impact to the point where soil particles detached (on-site) and sediment deposited (off-site). Erodibility varies with the soil texture, aggregate stability, shear strength, infiltration, and organic and chemical content. Climate, soil, topography and vegetation are the contributing factors to the soil erosion. The geological and accelerated are two general forms of soil erosion. Surface erosion may be classified according to the mechanism, which cause erosion. There are splash, sheet, rill and gully erosions. Soil erosion can be quantified using several techniques such as pin erosion, rill and gully, sediment yield, stream and channel, erosion plot (using soil erosion gauge) and universal soil loss equation methods.